El control interno y su relación con la gestión de tesorería en la Municipalidad Provincial de Requena, 2023 - Santillan Torres, Italo (2024)
The fundamental purpose of this research was to establish the relationship between internal control and treasury management in the Provincial Municipality of Requena in the year 2023. A descriptive-correlational study was carried out with a non-experimental design, using 98 employees as study population who were administered a questionnaire to collect information. The results revealed that internal control was evaluated as regular by 23%, as was treasury management. It is concluded that there is a significant positive assessment between both variables, supported by a coefficient of 0.828 and a significance value of 0.000. Furthermore, it was observed that the organizational dimension showed a coefficient of 0.683 and a significance of 0.000, while for the procedure a coefficient of 0.628 and a significance of 0.000 was obtained. Regarding the human resources dimension, a coefficient of 0.759 and a significance of 0.000 was recorded. Finally, in the supervision dimension, a coefficient of 0.743 and a significance of 0.000 was identified. All these findings indicate a significant relationship with treasury management in the Provincial Municipality of Requena in 2023.